Television and Family Unity in South – South Nigeria - Ufuophu-Biri, Emmanuel (Richtmann Publishing, 2020)
Television plays important role in the family. It serves as source of information, entertainment, cultural propagation, among other functions. It brings family members together and serves as a catalyst for family unity. However, there is the argument that television viewership could also have negative influence on family unity and values. The study therefore investigated the influence of Television viewing on family unity and values in Southern Nigeria. The study adopted the Behavior Imitation, Linkage and Bowen Family Systems theories. The study used survey and questionnaire as method and instrument respectively. The respondents were chosen through a multi-stage sampling process. The data were analyzed using descriptive statistics. The results show that majority of the respondents do not watch television together with other family members at home. Also, watching of television is found to have negative influence on family unity and values. The study recommends that family members should watch television together at home; and avoid adopting negative values they watch on television.